OC-144 The management of low-risk primary upper gastrointestinal haemorrhage in the community: a 5-year observational study. (28th May 2012) - McLaughlin, C; Dalton, H; Vine, L; Chapman, L; Deering, P; Whittaker, S; Beckly, J; Fortun, P; Murray, I; Hussaini, H; Michell, N; Stableforth, B; et al.
Abstract : Introduction: Acute upper gastrointestinal haemorrhage is a common medical emergency, initially managed with in-patient care. Bleeding stops spontaneously in over 80% of cases indicating patients with low-risk upper gastrointestinal haemorrhage may be more optimally managed in the community, without the need for admission to hospital. We have previously shown that using the Glasgow Blatchford Score (GBS) is an accurate method of identifying low risk cases. 1 2 Aims: To assess the safety of managing patients with low risk upper gastrointestinal haemorrhage without admission to hospital. Methods: Prospective/retrospective study of all patients presenting to a UK teaching hospital with low risk upper gastrointestinal haemorrhage who were managed without admission to hospital over 5 years. Low risk was defined as: GBS ≤2, age <70 years, no other active medical problems, not taking warfarin, suspected non-variceal bleed. Outcome measures were the need for intervention (blood transfusion, endoscopic therapy or surgery) and death. Results: 142 patients fulfilled the inclusion criteria, and were managed without admission to hospital. Upper GI endoscopy was preformed at a median of 1 day (range 0–18 days). No patients required endoscopic intervention, blood transfusion or surgery. The 28-day mortality was nil. 41 patients had a normal endoscopy. 11 had significant endoscopic findings (peptic ulceration =10, oozing Mallory Weiss tear =1) but did not require intervention. Significant endoscopic findings were unrelated to age (p=0.547), and four patients <30 years had significant findings (peptic ulceration n=3, Mallory Weiss tear n=1). Conclusion: Patients presenting with a primary upper gastrointestinal haemorrhage aged <70 years with a GBS of ≤2 are at low risk, and can be safely managed in the community. All such patients should have an upper GI endoscopy. The findings in this paper were presented to the NHS Innovation Challenge Prize Final, London, 29th September 2011. Competing interests: None declared. References: 1. Stanley AJ, et al. Lancet 2009;373 :42–7. 2. Stephens J . Eur J Gastro Hepatol 2009;21 :1340–6.